OPPORTUNITIES AND ADVANTAGES OF THE 24-HOUR BLOOD PRESSURE MONITORING IN CHILDREN AS PART OF THE OUTPATIENT EXAMINATION - A.E. Pal'tseva; E.V. Syutkina; O.V. Kozhevnikova; A.N. Rakhimova; O.D. Meshcheryakova; I.E. Smirnov; V.I. Tambovtseva (Union of pediatricians of Russia, 2009)
The 24 hour blood pressure monitoring has gone beyond the scope of the scientific research for the last decade and is now more widely used in practical healthcare, including pediatrics to identify changes of pressure both towards hypertension and hypotension. It is obviously advantageous to prove pathologic changes in the blood pressure level, as well as to give an objective evaluation of its intensity and duration. This article is devoted to identification of the diagnostic value for the daily blood pressure monitoring outpatient conditions and development of the optimal monitoring regimes to be used among children.Key words: 24 hour blood pressure monitoring, arterial hypertension, arterial hypotension, vegetovascular dystonia, children.